Effects of High-Voltage Overhead Power Lines (HVOPLs) on Residential Property Prices - Jayantha, Wadu Mesthrige; Abeydeera, Lebunu Hewage Udara Willhelm (Asian Journal of Economics and Empirical Research, 2020)
Research findings on the effects of high-voltage overhead power lines on values of neighborhood properties remain inconclusive and inadequately explored. This study aims to investigate the effects of HVOPLs on market values and sale-prices of residential properties in the vicinity. The empirical results based on a hedonic price model show that HVOTLs impart a significant negative effect on nearby residential properties. Results show that affected properties are selling at a discount price compared to properties without the influence of HVOPLs. The market value of a residential unit located within physical distance of 300-meters of power-lines, and pylon, are on average, 34.2% and 18% lower than comparable properties, respectively. Furthermore, results suggest that it is the physical distance to HVOPL structures that accounts more for the value diminution compared to the visual impact of the structure. The results imply that the market value of properties adjacent to HVOPL corridors is reduced significantly. This discourages potential property buyers. The study contributes to the knowledge in two-ways: (i) it shows the greater impact of HVOPLs on property prices with a larger reduction in valuation than previous studies; and (ii) effects of the different visual impact of pylons compared with that of cables are clearly distinguished.